An Advanced Characterization Toolbox for Selective Olefin Oxidation Catalysts. Issue 3 (18th January 2023) - Klag, Linda; Sheppard, Thomas L.; Grunwaldt, Jan‐Dierk
Abstract: The selective oxidation of propylene and isobutene form a central cornerstone in chemical industry, typically catalysed by bismuth molybdate based multicomponent systems. Over the past decades, a detailed knowledge has been gained on the mechanism by theoretical and experimental studies including in situ and operando characterization techniques, using simplified model catalysts. These have provided excellent insight, but in industrially applied selective oxidation typically multi‐component catalysts are used, leading to higher activity and selectivity. New concepts and characterization methods allow now studies of the more complex multicomponent catalysts covering the various length and time scales and potentially providing new insights into the dynamics and cooperation during catalysis. Starting with an overview of past concepts and milestones, we report on latest developments and future trends in the field of selective oxidation of lower olefins. Thereby we focus both on conventional spectroscopic and advanced characterisation methods and discuss the importance of integral and spatially‐resolved approaches. We conclude that fundamental understanding of such complex oxidation reactions requires combined and interdisciplinary research, now possible with the new characterization tools, data analysis schemes and reactor modelling approaches. This allows bridging the various complexity scales. Abstract : Advanced Characterization for Olefin Oxidation Catalysts : Selective olefin oxidations over bismuth molybdate based mixed metal oxide catalysts are highly complex and dynamic reactions. A holistic understanding of the catalytic processes includes knowledge about structure‐activity relationships on multiple time and length scales, as well as on all spatial dimensions. To tackle these criteria, a toolbox of complementary characterization techniques is presented within the scope of this concept article.